Anatomy of the Prostate Gland: Modalities and Techniques for Its Assessment - Mahadevan, Gowtham S.; Arunachalam, Venkatesh Kasi; Rajasekaran, Sriman; Kashyap, Ravindar; Gunasekaran, Kannan; Thirumoorthi, Suruthi (Journal of Gastrointestinal and Abdominal Radiology, 2024)
Prostate imaging is indispensable for the diagnosis and management of prostatic carcinoma and other prostate lesions. Understanding imaging anatomy is the basis for accurate diagnosis and standardized reporting of the prostatic lesions. In this article, we will discuss about general anatomy of the prostate, zonal anatomy, imaging techniques for its assessment, modality specific appearance of different zones of the prostate in detail.
Keywords: prostate anatomy; prostate cancer; prostate imaging; prostate MRI; prostate USG